The Routledge Handbook of Anthropology and the City
1 online resource (550 pages)
Keywords: The Routledge Handbook of Anthropology and the City provides a comprehensive study of current and future urban issues on a global and local scale. Premised on an ‘engaged’ approach to urban anthropology, the volume adopts a thematic approach that covers a wide range of modern urban issues, with a particular focus on those of high public interest. Topics covered include security, displacement, social justice, privatisation, sustainability, and preservation. Offering valuable insight into how anthropologists investigate, make sense of, and then address a variety of urban issues, each chapter covers key theoretical and methodological concerns alongside rich ethnographic case study material. The volume is an essential reference for students and researchers in urban anthropology, as well as of interest for those in related disciplines, such as urban studies, sociology, and geography.